3D spatial operations in geo DBMS environment for 3D GIS - Chen, Tet Khuan (Springer Berlin / Heidelberg, 2007)
Next generation of GIS software should be able to manipulate and analyse complex situations of real world phenomena. One of the desired components in such software or system is the geometric modeling that works with 3D spatial operations. This paper presents a portion of problem that we currently attempt to solve, that is the 3D spatial operations for Geo DBMS. Some popular spatial operations in 3D GIS for example 3D XOR, 3D union, 3D intersection, and 3D difference are vital for 3D spatial analysis and forms major discussion of this paper and part of our research effort to address the 3D GIS problem. To formulate this research in a suitable way, our approach is to develop the new 3D data type, polyhedron, within geo-DBMS. The basic idea is to relate the implementation of intersection point in 3D planar polygon (Chen and Abdul-Rahman, 2006) into the geometrical modeling for 3D spatial operations. The approach works and we highlighted the results by using the real world data sets. The research shows that the essential mathematical algorithms are applicable for real world objects and provides a solution towards a full 3D analytical operation in future.